Justice in Disarray? Assessing the Legitimacy of the Paris Agreement After the U.S. Withdrawal - Ave Agave Christina Situmorang; Winanda Kusuma; Reko Dwi Salfutra; Bunga Permatasari (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2025)
The issue of climate change is a global environmental challenge that requires comprehensive collaboration between countries. The Paris Agreement was born as an international legal instrument under the auspices of the United Nations Framework Convention on Climate Change (UNFCCC), with a nationally determined contributions (NDCs) approach and the principle of common but differentiated responsibilities. The United States, as one of the world's largest emitters, plays a key role in emissions reduction efforts and provides financial assistance to developing countries. However, the United States' unilateral decision to withdraw from the Paris Agreement during the Donald Trump administration, citing economic interests, has sparked debate regarding the binding force of international agreements. Through a normative legal approach and analysis of the 1969 Vienna Convention on the Law of Treaties, it was found that the United States' withdrawal contradicts the provisions of Article 62 concerning a fundamental change of circumstances. This situation demonstrates the dilemma between national sovereignty and compliance with global commitments. Therefore, strengthening the enforcement and implementation mechanisms of international agreements in the environmental sector is necessary to ensure the achievement of global ecological justice.